Frequency of oral habits and dentoalveolar alterations in children from 7 to 12 years at a dental teaching healthcare in Lima- Perú. Retrospective study - Vicente Ramos, Nadia Paola (2022)
Objective: The aim of this study was to determine the frequency of oral habits and dentoalveolar alterations in children from 7 to 12 years. Materials and methods: The study is descriptive, cross-sectional and a retrospective study. Children’s orthodontic medical records between 7 to 12 years were revised at the pediatric dentistry service of the Universidad Peruana Cayetano Heredia during the period 2015-2020. Results: 149 dental records were reviewed, 55.7% (n = 83) female and 44.3% (n = 66) were male. The prevalence of oral habits was 38.93%, the most frequent habits were tongue thrusting (21.48%), lip sucking (10.07%) and mouth breathing (8.72%). Transverse anomalies such as anterior crossbite (30.20%), vertical anomalies like deep bite (24.16%) and sagittal anomalies, such as class I malocclusion (57.72%), class II malocclusion (23.49%) and class III malocclusion (18.79%) were found. The congenital dentoalveolar alterations found was, absent permanent tooth (17.45%); and in other acquired alterations, midline deviation (79.87%), and dental crowding (77.86%). Conclusions: Tongue thrust is the most frequent oral habit. Other usual dentoalveolar anomalies are midline deviation, dental crowding and class I malocclusion.